The Bruce collection of Eskimo material culture from Kotzebue Sound, Alaska / Fieldiana, Anthropology, new series, no.1 - VanStone, James W. ([Chicago, Ill.] : Field Museum of Natural History, 1980)
Includes bibliographical references (p. 80-82). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).